Unveiling Tick Diversity in Cattle in Cameroon: Emergence of Rhipicephalus microplus, Replacing the Original Rhipicephalus spp. - Muhammad Umair Aziz; Jehan Zeb; Michel Lontsi-Demano; Angel Almendros; José de la Fuente; Olivier Andre Sparagano; Patrick Butaye (Veterinary Sciences, 2025)
Ticks are well-known vectors of pathogens, posing considerable risks to livestock health and productivity. In Cameroon, where livestock production is vital, established tick species such as Amblyomma variegatum and Hyalomma truncatum are prevalent in key cattle-rearing areas. The recent introduction of the invasive, acaricide-resistant Rhipicephalus microplus further complicates control efforts. In this study, we deliver baseline data on the composition of tick species and their shifts within agroecological zone I (AEZ I) and agroecological zone III (AEZ III) of Cameroon, providing a foundation for targeted vector control strategies to ultimately reduce the risk of pathogen transmission. From 1100 ticks collected across two Cameroonian agroecological zones, H. truncatum (39.9%), A. variegatum (31%), and R. microplus (10.64%) were the most prevalent species, along with Rhipicephalus lunulatus (4.45%), Hyalomma rufipes (1.45%), Hyalomma marginatum (1.09%), Hyalomma dromedarii (0.45%), and Rhipicephalus sanguineus (0.9%). Molecular identification using cytochrome C oxidase subunit 1 (cox1) and 16s led to the identification of five additional species, Hyalomma nitidum (0.73%), Rhipicephalus simus (3.54%), Rhipicephalus sulcatus (2.64%), Rhipicephalus praetextatus (2.1%), and Rhipicephalus pusillus (1.1%). R. microplus emerged as the most dominant Rhipicephalus spp. in AEZ I, comprising 67.5% of the total Rhipicephalus ticks. In conclusion, we demonstrate the further spread of R. microplus, which represents a major source of vector-borne diseases, affecting both humans and animals.